"A Blessing and a Curse:" Opioid Users' Perspectives on Naloxone and the Epidemic of Opioid Overdose. (1st May 2020) - Kline, Anna; Mattern, Dina; Cooperman, Nina; Dooley-Budsock, Patricia; Williams, Jill M.; Borys, Suzanne
Abstract: Background : To address the alarming rise in opioid overdose deaths, states have increased public access to the overdose reversal medication, naloxone. While some studies suggest that increased naloxone accessibility reduces opioid overdose deaths, others raise concerns about unintended consequences, such as increases in risky drug use and opioid re-use post-overdose to counter naloxone-induced withdrawal symptoms. Few studies have examined the impact of expanded naloxone access on the attitudes and behaviors of opioid users. Methods : In this qualitative study, we conducted in-depth, semi-structured interviews with 36 English-speaking opioid users 18+ years of age. Informants were recruited from an urban methadone clinic, a needle exchange program and a residential treatment program. The approximately hour-long interviews focused on users' attitudes and behaviors surrounding naloxone, opioid use and overdose. Transcribed audio-recordings of interviews were analyzed using NVivo. Results : Informants were ambivalent about naloxone, widely acknowledging its life-saving benefits while reporting such negative effects as severe withdrawal symptoms and the promotion of riskier drug use. Naloxone-induced withdrawal, coupled with misperceptions about naloxone's pharmacological effects, prompted overdose survivors to rapidly re-use opioids and refuse hospitalization following an overdose reversal. About half the sample believed naloxone led to greater risk-taking by others, such as fentanyl use or use in higher quantities, but did not endorse riskier drug use themselves. Conclusions : The results suggest the need for targeted education about the pharmacological effects of naloxone and better strategies for managing naloxone-induced withdrawal. Future research should focus on the extent to which naloxone is associated with greater opioid risk-taking.